MATHEMATICAL MODEL OF SHORT DISTANCE PISTOL SHOOTING PERFORMANCE IN EXPERIENCED SHOOTERS OF BOTH GENDER - Dopsaj, Milivoj; Marković, Stefan; Umek, Anton; Prebeg, Goran; Kos, Anton (NBP. Nauka, bezbednost, policija, 2019)
The aim of this paper is to determine the mathematical model of relation of accuracy and precision when shooting from a pistol Zastava CZ 99 in relation to gender and short target distance. The research included 49 participants (Men=27, Women=22). The testing was carried out using precision shooting from CZ 99 pistol on a Standard ISSF 25m precision pistol target on a 6, 10 and 15m distance (5 rounds per distance). The level of performance was evaluated in relation to accuracy and precision in the function of target distance. For the sample of men, the shooting accuracy was 76.98, 62.70 and 50.61%, while for the sample of women it was 60.32, 51.03 and 37.29% for the shooting distance of 6, 10 and 15m, respectively. The precision level was 8.52, 7.01 and 5.59 points (i.e. circles) for men and 6.63, 5.61 and 4.24 points for the women, respectively. The defined dependency models accuracy-distance and precision-distance have shown that: for men, the efficiency of shooting in relation to accuracy is decreasing 2.91%, i.e. 0.32 circles, while for women accuracy decreases 2.57%, i.e. 0.27 circles, for every meter of increase in distance.